A Pascal program for computing the DNA concentration in cellular homogenates - Sedo, A; Adamec, M (Computer methods and programs in biomedicine, 1990)
The use of manual graphical methods for evaluating the results of Brunk's fluorometric DNA concentration assay was found to be subjective and time-consuming. That is why a short program (in Turbo Pascal, version 4) for fluorometric data processing was designed.
Keywords: programovací jazyk; Fluorometry; Mathematical Computing; software; fluorometrie; Programming Languages; Software; DNA; matematické výpočty počítačové